Online vs. Classroom Learning: Examining Motivational and Self-Regulated Learning Strategies Among Vocational Education and Training Students - Quesada-Pallarès, Carla; Sánchez-Martí, Angelina; Ciraso-Calí, Anna; Pineda-Herrero, Pilar (Frontiers in Psychology, 2019)
Numerous studies have been conducted in order to explore motivational and self-regulated learning strategies (SRL) in students. Research highlights the importance of having motivated students equipped by strategies that help them self-regulate their learning, this being highly important when learning is acquired through online learning programs. Nonetheless, research in this area with Vocational Education and Training (VET) students has been scarce; this is the gap in the literature this paper aims to address. The article analyzes the level of motivational and SRL strategies among VET students by comparing them according to the learning modality chosen. In so doing, we applied a cross-sectional study using a quantitative approach. 577 first-year VET students responded an online questionnaire based on some of the motivational and SRL strategies scale of Pintrich’s model. Statistical analyses were applied to test two hypotheses. Pintrich’s model was validated through a confirmatory factor analyses considering its application to Catalan VET students for the first time. Results point out that there are significant differences between classroom and online students regarding their metacognitive self-regulation and effort regulation level, when starting a VET program; but this difference might not be entirely explained by the learning modality chosen. The findings of this study intend to help VET researchers and practitioners understand their students’ characteristics when starting the program in order to develop strategies to ensure their engagement throughout the course.